2005
DOI: 10.1523/jneurosci.1263-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of Aging: The Penetration of Cognition into Action Control

Abstract: Although functional imaging studies have frequently examined age-related changes in neural recruitment during cognitive tasks, much less is known about such changes during motor performance. In the present study, we used functional magnetic resonance imaging to investigate age-related changes in cyclical hand and/or foot movements across different degrees of complexity. Right-handed volunteers (11 young, 10 old) were scanned while performing isolated flexion-extension movements of the right wrist and foot as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
327
6
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(373 citation statements)
references
References 97 publications
(96 reference statements)
37
327
6
3
Order By: Relevance
“…Indeed, recent studies showed that older adults could reach levels of motor performance comparable to those obtained in young adults. However, to reach such levels of performance, older adults had to recruit additional attentional and cortical resources which could be interpreted as a compensating mechanism (Boisgontier et al 2012;Goble et al 2010a, b;Heuninckx et al 2004Heuninckx et al , 2005Heuninckx et al , 2008Hutchinson et al 2002;Mattay et al 2002;Naccarato et al 2006). This additional recruitment reduced the remaining attentional and cortical resources as evidenced by a degraded behavioural performance in older adults when the task complexity increased (Boisgontier et al 2012;Goble et al 2012b;Heuninckx et al 2004;Seidler et al 2002).…”
Section: Models Of Control and Internal Modelsmentioning
confidence: 99%
“…Indeed, recent studies showed that older adults could reach levels of motor performance comparable to those obtained in young adults. However, to reach such levels of performance, older adults had to recruit additional attentional and cortical resources which could be interpreted as a compensating mechanism (Boisgontier et al 2012;Goble et al 2010a, b;Heuninckx et al 2004Heuninckx et al , 2005Heuninckx et al , 2008Hutchinson et al 2002;Mattay et al 2002;Naccarato et al 2006). This additional recruitment reduced the remaining attentional and cortical resources as evidenced by a degraded behavioural performance in older adults when the task complexity increased (Boisgontier et al 2012;Goble et al 2012b;Heuninckx et al 2004;Seidler et al 2002).…”
Section: Models Of Control and Internal Modelsmentioning
confidence: 99%
“…The proprioception state may be even more challenging in older people and cause poor balance (Lin and Woollacott 2005) and irregularity of gait, especially with cognitive load (Shellenbach et al 2010). Research using fMRI has also identified an age-related shift from automatic to more cognitively controlled movements as subjects get older (Heuninckx et al 2005). In addition, elderly subjects were found to rely more on visual control when they learnt and performed a precision locomotor task (van Hedel and Dietz 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of this system is shown to change with age (Sharma & Baron, 2014;Ward, 2006;Ward & Frackowiak, 2003), which is associated with a decrease of action perception (e.g., accuracy of action prediction, Diersch et al, 2012) and action production (e.g., greater movement variability and deficits in coordination, Seidler et al, 2010). Furthermore, older adults compared to younger adults show activation in additional brain areas during movement execution, coordination and action perception (Diersch et al, 2016;Heuninckx et al, 2005;Heuninckx, Wenderoth, & Swinnen, 2008. As age advances, action perception and production might be increasingly associated with the activation of motor programs that are irrelevant for the on-going task.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this notion, the sensorimotor system undergoes age-related changes (Heuninckx, Wenderoth, Debaere, Peeters, & Swinnen, 2005;Sharma & Baron, 2014;Ward, 2006;Ward & Frackowiak, 2003). On the behavioural level, these changes result in greater movement variability, general slowing of movements and coordination deficits with increasing age (Seidler et al, 2010).…”
mentioning
confidence: 94%